Artist as teacher and model. Issue 3 (1st December 2019) - Yeager, Raymond
AbstractBeing an artist is often an enigma to art students. They need a model who will demonstrate a way to navigate the world as an artist. We are that model. As art educators, we can help demystify the practice of being an artist and help our students understand it by offering ourselves as models and mentors. In this undertaking, we should be open with students about our own odysseys as artists. Especially the many failures and hardships we faced and overcame to succeed. This modelling of art practice is a form of 'lending consciousness'. Developed by Russian psychologist Lev Vygotsky, this concept asserts the idea that development is a social or communal process as well as a pedagogical one. By creating a learning environment where we model, as well as instruct, we alter the traditional role we play in the classroom. When our teaching and art-making become intertwined, the students benefit greatly from a more engaged instructor, and it is more likely that they will see themselves as artists-in-training.